Antigua and Barbuda : Staff Report for the 2014 Article IV Consultation and Second Post-Program Monitoring. (IMF Staff Country Reports; Country Report, 2015)
KEY ISSUES Context. The new government that came to power in June 2014 inherited serious fiscal and external payments problems, including arrears to the Fund and other creditors, and unresolved banking sector problems. Moreover, public debt remains at an unsustainable level of close to 100 percent of GDP, while economic activity has been weak with output still well below the level reached at the time of the 2008/09 global financial crisis. Main policy recommendations -- Implement fiscal measures equivalent to 2.8 percent of GDP in 2015 to tackle cash flow problems and achieve an underlying primary surplus of 3.0 percent of GDP by 2016 to address debt sustainability challenges. Underpin measures with structural fiscal reforms. -- Use Citizenship by Investment Program revenues to pay down arrears and debt and fund bank resolution. The program should be managed in line with the high standards of governance and transparency set out in the law. -- Move expeditiously as planned with the resolution of ABI Bank and support initiatives underway to strengthen the regional bank resolution framework, in particular, the passage of needed legislative reforms. -- Improve competitiveness by moderating labor costs; increasing energy efficiency, including by better performance of the state-owned utility company; and improving the investment climate. Authorities' views. The authorities broadly agreed with staff's assessment of the economic situation and risks, and its recommendations to reduce fiscal vulnerabilities and strengthen the banking system. They were more optimistic about growth prospects for 2015 based on expectations for substantial FDI. They are opposed to increases in taxes and plan to focus fiscal efforts on cutting recurrent spending. On bank resolution, they wish to work closely with the Fund and World Bank to speedily address outstanding problems. They paid the arrears to the Fund and committed to timely servicing of Fund obligations. Data provision. Data provision is adequate for surveillance and post-program monitoring although significant areas for improvement remain, in particular on labor market statistics, measurement of arrears, financial information on state-owned enterprises, and national accounts by expenditure components.